CONSUMER CULTURE IN THE FRENCH-LANGUAGE FASHION DISCOURSE: A LINGUOPRAGMATIC ASPECT - Hnoiova , Yaroslavna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The culture of consumption in the French-language fashion discourse, and also considers the linguistic and pragmatic aspect are analyzed in this article. It is found that the texts of glossy magazines use techniques of suggestion and1 infection in order to increase sales, popularize certain trends by involving celebrities in discussions, and use certain words and constructions to impose the importance of a new trend. To achieve this goal, the media influence people by trying to evoke emotions from the text they read, the photo they attach, and the advertisement of products. This directly affects the increase in consumption by users who are trying to keep up with the trend to bring themselves closer to the upper class, which has access to all the resources, so knowing the methods of influencing the human psyche, sales are growing, which directly leads to the problem of consumerism in modern society. The article highlights the importance of the fashion aspect in human life, the psychological methods of influence on a person used by the fashion industry, and analyzes the verbal methods of influence. _____________ References: • Baudrillard, Jean. La société de consommation: ses mythes et ses structures (1970). • Bauman, Consuminng Life (Cambige: Polity press, 2007), 160. • Сohen, , Kennedy, P. Global Sociology, 2-nd ed. (N.Y.: Macmillan, 2007), 584. • Lysenko, (2018). Internet-dyskurs mody: sutnist ta osoblyvosti v suchasnomu prostori. Vyshcha osvita Ukrainy u konteksti intehratsii do yevropeiskoho osvitnoho prostoru 81 (III) (2018): 169-174. • Nechyporenko, «Semiotychni horyzonty doslidzhennia mody.» Liudynoznavchi studii (Drohobych, 2009). • Baudrillard, Jean. Requiem pour les media (1971). • Spencer, Herbert. The Principles of Sociology2 (New York: D. Appleton and Company, 1898). • Tatenko, O. Sotsialna psykholohiia vplyvu: monohrafiia (Kyiv: Milenium, 2008), 216. • https://www.vogue.fr/article/tendance-pantalon-puddle • Santos, Diana, Belinda, Maia. «Language, emotion, and the emotions: The multidisciplinary and linguistic background.» Language and Linguistics Compass12 (6) (2018), https://compass.onlinelibrary.wiley.com/doi/abs/ 10.1111/lnc3.12280 • https://www.vogue.fr/mode